Implementasi Penataan Arsip Dinamis Berbasis Google Form Pada Umkm Kedaishi Ramen Kota Malang - Asura Ananada Rahmat; Fahmi Muhammad Az Zuhri (Advances In Education Journal, 2026)
This research addresses the issue of limited human resources in MSMEs, which often leads to neglected archival management. Consequently, business information records are not well-documented, increasing the risk of losing essential archives. Furthermore, retrieving archives becomes difficult due to the absence of a classification system. This phenomenon is observed at Kedaishi Ramen, an MSME in Malang City. Therefore, this study aims to develop and implement a Google Form-based records management system to improve the efficiency of operational data management at Kedaishi Ramen, thereby minimizing record loss and facilitating easier retrieval when needed. This study employs a qualitative approach with action research methods. The qualitative approach was chosen to gain a deep understanding of the dynamic records management process at Kedaishi Ramen, while the action research method was selected to provide direct practical solutions to their archival challenges. The results indicate that Kedaishi Ramen requires a structured, efficient, digital, and easy-to-implement archival system and guidelines to optimally support administrative activities. Before designing the dynamic records management manual, an initial management process was conducted on existing archives to identify their current condition, types, and the storage systems previously applied. Records management encompasses all tasks related to the administration of archives, including recording, monitoring, distribution, storage, maintenance, supervision, transfer, and disposal. However, at Kedaishi Ramen, these processes were adjusted to fit the existing situation and conditions. The archival management guidelines were developed in the form of a flowchart illustrating the workflow from the creation or receipt of documents to the final storage process in binders (ordners).